Binding of the Molecular Chaperone alpha B-Crystallin to A beta Amyloid Fibrils Inhibits Fibril Elongation - Shammas, SL; Waudby, CA; Wang, SY; Buell, AK; Knowles, TPJ; Ecroyd, H; Welland, ME; Carver, JA; Dobson, CM; Meehan, S (CELL PRESS, 2011)
The molecular chaperone alpha B-crystallin is a small heat-shock protein that is upregulated in response to a multitude of stress stimuli, and is found colocalized with A beta amyloid fibrils in the extracellular plaques that are characteristic of Alzheimer's disease. We investigated whether this archetypical small heat-shock protein has the ability to interact with A beta fibrils in vitro. We find that alpha B-crystallin binds to wild-type A beta(42) fibrils with micromolar affinity, and also binds to fibrils formed from the E22G Arctic mutation of A beta(42). Immunoelectron microscopy confirms that binding occurs along the entire length and ends of the fibrils. Investigations into the effect of alpha B-crystallin on the seeded growth of A beta fibrils, both in solution and on the surface of a quartz crystal microbalance biosensor, reveal that the binding of alpha B-crystallin to seed fibrils strongly inhibits their elongation. Because the lag phase in sigmoidal fibril assembly kinetics is dominated by elongation and fragmentation rates, the chaperone mechanism identified here represents a highly effective means to inhibit fibril proliferation. Together with previous observations of alpha B-crystallin interaction with alpha-synuclein and insulin fibrils, the results suggest that this mechanism is a generic means of providing molecular chaperone protection against amyloid fibril formation.